Non-Cash Instruments and Money Supply in Indonesia During Pandemic Covid-19 - Skolastika Ferlicia; Suhel Suhel; Sri Andaiyani (Signifikan: Jurnal Ilmu Ekonomi, 2022)
The emergence of the Covid-19 pandemic phenomenon at the end of 2019 caused non-cash transactions to increase, but several macro variables decreased. The study investigates the relationship between Non-Cash Transactions (through APMK and E-money proxies), National Income (GDP), Money Supply (M0), and Velocity of Money with the Vector Auto Regression method. The data was used from 2010 to 2021 at three different times, before Covid-19 and during Covid-19. Our result confirms that there was a relationship between money supply and non-cash transactions, the positive response occurred in all periods, and the negative response occurred during the Covid-19 pandemic. National income positively impacts money supply and velocity of money during all periods and Covid-19. It implicates that electronic money should be increased because it accelerates the circulation of money and can increase the flow of goods and services.How to Cite:Ferlicia, S., Suhel, S., & Andaiyani, S, (2022). Non-Cash Instruments and Money Supply in Indonesia During Pandemic Covid-19. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 383-398. https://doi.org/10.15408/sjie.v11i2.26491.JEL Classification: E41, E52